Reinterpretation of “Fitna” in QS. Al-Baqarah Verse 191 (Ma'na Cum Maghza Approach) - Hakam Al-Maâ€™mun; Haris Fatwa Dinal Maula (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
The meaning of the word â€œfitnaâ€ in Indonesian is often incorrect when it is associated with the word of Allah written in QS. al-Baqarah: 191. The snippet of the verse is al-fitna asyaddu min al-qatl, which if translated reads more or less